Risk Driving Review from Big Five Personality - Chrisnatalia, Maria; Jie, Lie; Jixiong, Cai; Wei, Zhang (World Psychology, 2023)
Accidents that occur due to drivers who tend to drive with a high risk. Vehicle users tend to drive recklessly and pass-through traffic which is called the risk of driving, this is influenced by internal and external factors. The purpose of this study is to look at the risk of driving in terms of five personalities and which personality types tend to lead to driving. The technique used is quantitative, with a sample of 100 participants. The sampling technique in this study was purposive sampling. How to collect data using google forms. Data analysis technique with simple regression test. Based on the hypothesis test, it was found that there is a relationship between agreeableness and neuroticism personality types on the risk of driving and Constiusness, Openess to experience and Extraversion have no relationship with the risk of driving. These results mean that the proposed hypothesis is accepted.